2018
DOI: 10.3892/ol.2018.8232
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis of diffusion weighted imaging for the evaluation of glioma heterogeneity based on different regions of interest

Abstract: Abstract. The present study aimed to explore the role of texture analysis with apparent diffusion coefficient (ADC) maps based on different regions of interest (ROI) in determining glioma grade. Thirty patients with glioma underwent diffusion-weighted imaging (DWI). ADC values were determined from the following three ROIs: i) whole tumor; ii) solid portion; and iii) peritumoral edema. Texture features were compared between high-grade gliomas (HGGs) and low-grade gliomas (LGGs) using the non-parametric Wilcoxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…From the 394 interpretation of the features and the results described above, it could be deduced that 395 LGGs had a more heterogeneous texture than HGGs, specifically in the T 2 contrasts; 396 and HGGs had a more heterogeneous texture than LGGs, specifically in the T 1Gd 397 contrasts; in both cases studying the NCR/NET region. Several works have reported 398 models whose main classification variable was heterogeneity of gliomas [18,23,25,[47][48][49]. 399 For example, through texture analysis applied on diffusion tensor imaging [25,49] and 400 diffusion kurtosis imaging [49] maps, diverse features that characterized the 401 heterogeneity of gliomas indicated an increased heterogeneity for higher grade gliomas 402 compared to lower grade gliomas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From the 394 interpretation of the features and the results described above, it could be deduced that 395 LGGs had a more heterogeneous texture than HGGs, specifically in the T 2 contrasts; 396 and HGGs had a more heterogeneous texture than LGGs, specifically in the T 1Gd 397 contrasts; in both cases studying the NCR/NET region. Several works have reported 398 models whose main classification variable was heterogeneity of gliomas [18,23,25,[47][48][49]. 399 For example, through texture analysis applied on diffusion tensor imaging [25,49] and 400 diffusion kurtosis imaging [49] maps, diverse features that characterized the 401 heterogeneity of gliomas indicated an increased heterogeneity for higher grade gliomas 402 compared to lower grade gliomas.…”
mentioning
confidence: 99%
“…Several works have reported 398 models whose main classification variable was heterogeneity of gliomas [18,23,25,[47][48][49]. 399 For example, through texture analysis applied on diffusion tensor imaging [25,49] and 400 diffusion kurtosis imaging [49] maps, diverse features that characterized the 401 heterogeneity of gliomas indicated an increased heterogeneity for higher grade gliomas 402 compared to lower grade gliomas. Moreover, Kin et al [47] studied the texture matrix 403 called Grey Level Co-occurrence Matrix (GLCM) of contrast enhanced T1 MR and 404 ADC maps and reported higher values of entropy (or non-uniformity) as well as reduced 405 values of homogeneity for HGGs when these were compared to LGGs.…”
mentioning
confidence: 99%
“…Twenty-nine articles were irrelevant and three could not provide sufficient data to construct the 2×2 table. According to the inclusion criteria, six studies8 11–15 were retrieved. The study selection process is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Some reports have suggested that TA holds promise in the field of oncology diagnosis, including quantifying tumour heterogeneity and tumour grading 10 11. Until now, some reports have been published regarding tumour heterogeneity in glioma using MRI TA 8 11–15. However, these studies were inconclusive because of insufficient samples and different diagnostic algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…"Radiomics", which is de ned as the high-throughput extraction of image features from radiographic images, has potential to provide a detailed pre-operative evaluation method of tumor heterogeneity. [11][12][13][14][15][16][17] This method of imaging analysis utilizes algorithms to derive image texture. At present, the most commonly used image texture analysis methods are rst and second order statistical method analyses of image pixels and their neighborhood gray level.…”
Section: Introductionmentioning
confidence: 99%